The Relationship Between Surface Water Quality And Mangrove Density On Pasaran Island, East Telukbetung District, Bandar Lampung City - Jundy Zaky Makarim; Slamet Budi Yuwono; Indra Gumay Febryano; Arief Darmawan; Irwan Sukri Banuwa (Journal of Tropical Marine Science, 2025)
The decline in mangrove land cover is a serious concern, because it can increase the possibility of sea water intrusion in coastal areas. This research aims to assess the relationship between surface water quality and mangrove density on Pasaran Island. The data obtained were analyzed using the multiple linear regression method to evaluate the simultaneous influence of mangrove density and sampling zone on various water quality parameters, including salinity, dissolved oxygen, electrical conductivity, total dissolved solids, and pH. The research results show that the denser the mangrove density, the lower the salinity level, but the density does not affect other water quality parameters, such as: dissolved oxygen, electrical conductivity, total dissolved solids, pH. The sampling zone also influences several water quality parameters, where zones closer to the coastline show higher parameter values ​​than transition zones or those further from the coast. External factors such as sea water intrusion and domestic waste pollution play a greater role in influencing water quality. The government should make efforts to conserve and rehabilitate forests and mangrove lands, especially in urban areas.